The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1158/1078-0432.ccr-16-2203
|View full text |Cite|
|
Sign up to set email alerts
|

Human Papillomavirus Regulates HER3 Expression in Head and Neck Cancer: Implications for Targeted HER3 Therapy in HPV+ Patients

Abstract: Purpose Human papillomavirus (HPV) 16 plays an etiologic role in a growing subset of HNSCCs, where viral expression of the E6 and E7 oncoproteins are necessary for tumor growth and maintenance. Although patients with HPV(+) tumors have a more favorable prognosis, there are currently no HPV-selective therapies. Recent studies identified differential receptor tyrosine kinase (RTK) profiles in HPV(+) vs. HPV(−) tumors. One such RTK, HER3, is overexpressed and interacts with phosphoinositide 3-kinase (PI3K) in HPV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 56 publications
(68 reference statements)
3
52
0
Order By: Relevance
“…The discrepancy was addressed with a recent study investigating the relationship between HPV oncoproteins and HER3-mediated signaling, and the role of HER3 as a potential molecular target in HPV-positive HNSCC [97]. This study proposed a novel mechanism by which HPV can promote tumor growth through the mTOR/AKT/PI3K pathway.…”
Section: Transcriptome-level Alterations Of Hpv-related Hnsccmentioning
confidence: 99%
See 4 more Smart Citations
“…The discrepancy was addressed with a recent study investigating the relationship between HPV oncoproteins and HER3-mediated signaling, and the role of HER3 as a potential molecular target in HPV-positive HNSCC [97]. This study proposed a novel mechanism by which HPV can promote tumor growth through the mTOR/AKT/PI3K pathway.…”
Section: Transcriptome-level Alterations Of Hpv-related Hnsccmentioning
confidence: 99%
“…They found that E6/E7 gene silencing led to diminished HER3 production, while increased E6/E7 oncoprotein production led to increased HER3 production. The results indicate a relationship between HPV infection and HER3 expression that is mediated by the E6 and E7 oncoproteins [97]. …”
Section: Transcriptome-level Alterations Of Hpv-related Hnsccmentioning
confidence: 99%
See 3 more Smart Citations